2007
DOI: 10.1186/gb-2007-8-9-r189
|View full text |Cite
|
Sign up to set email alerts
|

Social regulation of gene expression in human leukocytes

Abstract: Effects of loneliness on gene expression

Analysis of differentially expressed in circulating leukocytes from people who chronically experienced high versus low levels of subjective social isolation (loneliness) revealed over-expression of some anti-inflammatory genes and under-expression of some pro-inflammatory genes.

Abstract Background: Social environmental influences on human health are well established in the epidemiology literature, but their functional genomic mechanisms are unclear. The present …
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
577
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 615 publications
(627 citation statements)
references
References 69 publications
45
577
2
3
Order By: Relevance
“…Analyses of promoter TFBM distributions tested for differential expression was using an independent sample t-test with Welch's correction for heteroscedasticity (Miller 1986). To confirm the statistical significance of differential TFBM distributions, we carried out randomization tests as previously described (Cole, Galic et al 2003;Cole, Hawkley et al 2007). Briefly, the total set of 10 samples was randomly partitioned into two groups of 5 samples, differentially expressed genes were identified based on ≥ 2-fold difference in mean expression level, and the resulting difference in the frequency of target TFBMs was quantified.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Analyses of promoter TFBM distributions tested for differential expression was using an independent sample t-test with Welch's correction for heteroscedasticity (Miller 1986). To confirm the statistical significance of differential TFBM distributions, we carried out randomization tests as previously described (Cole, Galic et al 2003;Cole, Hawkley et al 2007). Briefly, the total set of 10 samples was randomly partitioned into two groups of 5 samples, differentially expressed genes were identified based on ≥ 2-fold difference in mean expression level, and the resulting difference in the frequency of target TFBMs was quantified.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…And high lonely group differed from low lonely group not only on a lower household income of mean 425,000 versus 916,000 yearly but also less married percentage in marital status. The characteristics of psychological participants of high lonely and low lonely groups were listed in Table 1 (Cole et al, 2007). Among the table, the revised UCLA loneliness scale was used for measuring the loneliness that had become the most common instrument used by researchers in assessing feelings of loneliness since 1980 (Russell et al, 1980) And the center for epidemiological studies depression scale (CESD) was a 20-item measure that assesses depressive symptoms, and scores of 16 or higher have been associated with clinical depression.…”
Section: Loneliness-associated Genesmentioning
confidence: 99%
“…Holwerda et al, found that mortality hazard ratio for feeling of loneliness was 1.3 in men, 1.04 in women with a 10-year follow-up of 4,004 older persons (Holwerda et al, 2012). In 2007, Cole et al, first provided that subjective social isolation was associated with human genome-wide transcriptional activity, including inhibiting anti-inflammatory transcription and promoting proinflammatory pathways (Cole et al, 2007). Furthermore, Lutgendorf et al (2009) validated that high depression and low social support was relative to increased activity of β-adrenergic transcription control, which promotes tumor progression in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…His first foray, published in 2007, looked at loneliness 4 . Social isolation is one of the most powerful known psychological risk factors for poor health, but it is never certain whether it causes the health problems, or whether a third factor is involved: lonely people might be less likely than others to eat well, for example, or to visit their doctor regularly.…”
Section: Worried Sickmentioning
confidence: 99%